Simple vaginal trachelectomy in women with early-stage low-risk cervical cancer who wish to preserve fertility: the new standard of care?. Issue 7 (3rd June 2020) - Plante, Marie; Renaud, Marie-Claude; Sebastianelli, Alexandra; Gregoire, Jean
Abstract : Objective: There is a trend toward less radical surgery in women with small-volume disease who wish to preserve fertility. The objective of our study was to evaluate the oncologic and obstetrical outcome of simple vaginal trachelectomy and lymph node assessment in patients with low-risk early-stage cervical cancer (<2 cm). Methods: From May 2007 to January 2020, 50 patients underwent a simple vaginal trachelectomy/conization with laparoscopic sentinel lymph node mapping±complete pelvic node dissection. Patients underwent loop electrocautery excision (LEEP), cone/cervical biopsies, or simple trachelectomy. A preoperative pelvic MRI with gadolinium contrast was systematically performed in all cases. The size of the lesion was established by review of the LEEP, cone or trachelectomy specimen, MRI, and clinical examination. Data was collected prospectively in a computerized database. Descriptive statistics and the Kaplan–Meier estimate were used for analysis. Results: The median age was 29 years (range: 21–44) and 35 (70%) patients were nulliparous. As per FIGO 2009 classification, 11 patients had stage IA1 with lymphovascular space invasion (LVSI), 13 patients had stage IA2, and 26 patients had stage IB1. Twenty-six patients had squamous histology, 20 patients adenocarcinoma, and four patients other histologies. On final pathology, lymph nodes were negative in 46 patients (92%), three patients had isolated tumor cells, and one patient had micrometastasis. Thirty patients (60%) had either no residual disease in the trachelectomy specimen (22) or residual dysplasia only (eight). With a median follow-up of 76 months (range: 1–140), only one local recurrence occurred which was treated initially with chemoradiation. She recurred again locally and underwent a pelvic exenteration: the patient progressed again and died of disease. The 5-year progression-free survival and overall survival was 97.9% and 97.6%, respectively. There were 40 pregnancies: five (12.5%) ended in the first trimester, one (2.5%) in the second trimester, and three (7.5%) were late preterm: all the others (30 or 75%) delivered >36 weeks and one pregnancy is ongoing. Conclusion: Simple trachelectomy/conization and lymph node assessment is an oncologically safe fertility-preserving surgery in well-selected patients with low-risk early-stage cervical cancer (<2 cm). Obstetrical outcomes are comparable to the general population.